Governance Dynamics in Times of Crisis: The Impact of Institutional and Foreign Ownership on Indonesian Firm Performance during the COVID-19 Period - Yoga Pratama Nugroho; Gustita Arnawati Putri; Shinta Nastitie Komalasari; Ahmad Dzakiyuddin; Made Wedaswari; Annisa Nur Safitri; Alifa Putri Khauriyah (Jurnal Riset Akuntansi, 2026)
This study investigates the effects of institutional ownership (IO) and foreign ownership (FO) on the performance of non-financial firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2025. Grounded in agency theory and the resource-based view, the study employs fixed-effects multiple regression with year and industry controls across the full sample (n = 3,621) and phase-partitioned subsamples representing the COVID-19 and post-pandemic periods. Additional threshold analyses are conducted to detect nonlinear ownership effects. The results reveal that institutional ownership exerts a negative effect on ROA, consistent with the entrenchment effect and the principal-principal conflict prevalent in Indonesia’s concentrated ownership environment. Conversely, foreign ownership demonstrates a positive and significant performance effect, supporting the hypotheses of governance and resource transfer. Both effects are concentrated in the post-pandemic period and are insignificant during the pandemic phase. Threshold analyses further establish that these relationships are nonlinear: the negative institutional ownership effect manifests at low-to-moderate concentration levels (10%–40%) and reverses to positive only beyond the 90% threshold, whereas the positive foreign ownership effect emerges only after crossing a critical mass of approximately 60%–70%. These findings contribute to the literature by demonstrating that the performance implications of block ownership are contingent on investor origin and ownership scale, with important implications for minority investor protection policy in emerging markets.